Analysis Need Education for Postpartum Mothers - Runiari, Nengah; Ruspawan, Dewa Made; Suratiah, Suratiah (Poltekkes Kemenkes Surakarta, 2023)
Background: Postpartum mothers need education to maintain themselves and their babies. Only a little study about material education is based on what a mother and husband need. The study aims to explore the need for education for postpartum mothers and identify materials, methods, and educational media needed by postpartum mothers. Methods: This study employed mixed methods with a sequential exploratory design. Stage 1 was done through a qualitative study with in-depth interviews with the seven participants using purposive sampling. Analyze the data with thematic deductive analysis. The quantitative phase used 300 postpartum mothers with a purposive sampling technique. An instrument study questionnaire was prepared by researchers, and a trial was conducted on 50 respondents with valid and reliable results. Quantitative data analysis with descriptive analysis Results: It found six themes, namely